Air plasma sprayed high-entropy AlCoCrFeNiY coating with excellent oxidation and spallation resistance under cyclic oxidation at 1050–1150 °C. (15th April 2022) - Lu, Jie; Chen, Ying; Sun, Zihao; Li, Ling; Liu, Xuanzhen; Huang, Aihui; Zhang, Han; Guo, Fangwei; Zhang, Xiancheng; Zhao, Xiaofeng
Abstract: An AlCoCrFeNiY high-entropy alloy coating was prepared using air plasma spray. The cyclic oxidation behavior of the coating was investigated and compared with that of a conventional NiCoCrAlY coating. It is demonstrated that the AlCoCrFeNiY coating exhibits much stronger resistance to oxidation and spallation than the NiCoCrAlY coating when they are thermally cycled between room temperature and 1050- 1150 °C. The difference is attributed to a much lower growth rate of the oxide scale on the AlCoCrFeNiY coating as a result of its significantly higher activation energy of oxidation and the absence of spinel. Graphical Abstract: ga1 Highlights: The spallation resistance of high-entropy AlCoCrFeNiY coating is highly superior to the conventional NiCoCrAlY coating. The oxidation rate of AlCoCrFeNiY coating is much lower than that of NiCoCrAlY coating. The activation energy of oxidation for AlCoCrFeNiY coating is much higher than that of NiCoCrAlY coating. The formation of detrimental spinel oxides is suppressed in the early oxidation stage for the AlCoCrFeNiY coating.